Prarancangan Pabrik Tetraklorosilane dari Rice Husk Ash Kapasitas 10.000 Ton/Tahun - , HUMAM BAIQUNI, Ir. M. Fahrurrozi, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is an agricultural country which is rich in natural resources. One of the main result is rice from farming. One of the largest components contained in rice husks is silica (SiO2) that is equal to 20%. Rice husk until now has not been utilized optimally and economic value is still very low. Silica can be used for a variety of industries and can also be used as raw material to produce tetrachlorosilane (SiCl4). SiCl4 is widely used in the semiconductor industry, photovoltatic cells, silicone resins, and also the manufacture of pure silicone. Tetrachlorosilane from rice husks is produced through three main stages, the first stage is the removal dirt, the second stage is the combustion of rice husk to produce ash that contains SiO2 and carbon, and the last stage is the reaction between silica ash with Cl2 gas to produce the gaseous SiCl4. SiCl4 gas is condensed to get SiCl4 in liquid phase as products that have purity of 99% by weight. The raw material is obtained from rice mill places around the Kerawang and Cl2 gas is obtained from PT. Mahkota Indonesia. While supporting materials such as H2SO4 is obtained from PT. Indonesia Acid Industry. Rice husk required for the main process as much as 1392.4 kg / hr and chlorine gas are needed as much as 1179.4 kg / hr, while supporting materials such as H2SO4 required 19.76 kg / hr and water as much as 71.63 kg / hr. In unit of utility, the total water requirement is 18336.05 kg / hr, power requirements at 1,197,792 kWh needs fuel in the form of natural gas and diesel 0,65 MMBTU / hr of 1154.54 kg / year, and the need for compressed air at 30.56 m3/hr. Fixed capital required for the establishment of SiCl4 plants is Rp 50,096,637,685.80 and $ 7,355,752.48. Working capital needed is Rp 32,959,814,415.41 and $ 1,042,208.91. Profits earned before tax amounted to Rp 72,815,167,016.85 / year and profit after tax was Rp 36,407,583,308.43 / year. From the results of calculations, the Return of Investment (ROI) before taxes is 59.60%, Return of Investment (ROI) after taxes is 29.80%, Pay Out Time (POT) before taxes is 1.44 years, Pay Out Time (POT) after tax is 2,51 year. Break Event Point is 43.7363% , Shut Down Point is 29.5748% and Discounted Cash Flow Rate of Return is 46.52%.Based on the economic evaluation, the establishment of Tetrachlorosilane plan from Rice Husk with a capacity of 10,000 tons / year interesting and profitable be further assessed.